(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The exponential growth of network users has to lead to poor management of networks that use the traditional networking approach. Traditional networking approaches have become an overhead in terms of flexibility, innovations, complexity, and programmability among the network. SDN guarantees a holistic approach to network flexibility and programmability. Network visibility in SDN gives scope for rapid innovation. SDN being a new paradigm, less work has been done towards security. Security is one of the biggest concerns in SDN. Separation of control and data plane in SDN has to lead to the emergence of Denial of Service (DoS) attack. The centralized controller in SDN makes it the best target for attackers and acts as a single point of failure. Attacks on the SDN controller can bring the entire network down. This paper presents an approach to monitor traffic and we propose a novel method to mitigate these anomalies and attacks in the network. We believe that the DoS attack can be toned down using this new technique.